Identifikasi dan Pengenalan Tanaman Obat di Kelurahan Mudung Laut, Kota Jambi - Pratiwi, Puspa Dwi; Pratama, Septa; Aghadiati, Faradina (Studium: Jurnal Pengabdian Kepada Masyarakat, 2022)
High prevalence of traditional medicine used as a promotive, preventive and curative for disease is still a choice among the community, especially during the transition period of the COVID-19 pandemic, one of which is the community in RT 09 Mudung Laut Village, Pelayangan District, Jambi City. Community service in Mudung laut was carried out to maximise the benefits of plants as traditional medicine and providing information to the people of Mudung Laut Village regarding the identification and introduction of medicinal plants so that the community can process medicinal plants properly without destroying the active substance content. The method of community service carried out was through preparation stages, implementing the service in the form of socializing material with some themes and the final stage was searching for medicinal plants around the house and processing ginger into powder and granule. The results of this community service were the development of skills and knowledge, list of medicinal plants around Mudung Laut Village, increasing added value and creating jobs as well as product diversification. Furthermore, it is hoped that this community service activity will carry out continuous assistance and cooperation in Mudung Laut Village so that the community and implementers can transfer knowledge and create innovations to improve the level of public health.